PERANCANGAN LOGO MEMAYU HAYUNING SURABAYA UNTUK PENINGKATAN NASABAH BANK SAMPAH INDUK SURABAYA - Shafira Qiddist Sayyida (Jurnal Vicidi, 2020)
Bank Sampah Induk Surabaya is one of non profit organization in Surabya. To increase customers of Bank Sampah Induk Surabaya, there is a social campaign called Memayu Hayuning Surabaya. Social campaigns require logos as identity or differentiator with other organizations. In the making, the logo needs identification, color selection, and many things that need to be done to create the logo, in the design of the logo Memayu Hayuning Surabaya, tere is a lot of research to the creation of the final logo. Memayu Hayuning Surabaya is a social campaign engaged in the environment control, so that the logo used has a green color with Javanese accents because the name of the campaign is in Javanese language. The elements contained in the logo are also through the selection adjusted to the character of the social campaign to be performed. So the logo according to the approach should be. Keywords: Logo, design, design, identification